Optimised synthesis of monoanionic bis(NHC)-pincer ligand precursors and their Li-complexes - Jürgens, Eva; Buys, Kai N.; Schmidt, Anna-Theresa; Furfari, Samantha K.; Cole, Marcus L.; Moser, Michael; Rominger, Frank; Kunz, Doris (New journal of chemistry, 2016)
Herein we report the optimised synthesis of a versatile bis(imidazole)carbazole framework 4, a precursor to our previously reported C-N-C bis(NHC) pincer ligand, bimca. We have also used 4 as a basis for constructing a library of fully characterised bis(imidazolium) salt pre-ligands which vary the steric and electronic parameters of the subsequently formed NHC moieties. Lithium bis(NHC)carbazolide complexes Li(bimcaR) were generated from their parent bis(imidazolium)carbazole salts, and their behavior in solution and the solid state is discussed.
Gesehen am 06.05.2020